Castration: an alternative punishment for rape offenders in Malaysia / Izyan Ithnain and Shazrina Abdul Malik - Ithnain, Izyan; Abdul Malik, Shazrina (2008)
This project paper is significant as there is no proposal that has been made to recommend castration as one of the alternative punishment for rape offenders in Malaysia in the Penal Code, despite the fact that the number of rape cases in Malaysia is increasing and most of the victims are children aged from seven years old. The relevancy of this research is to acknowledge every possible rapist as well as the offenders and to recommend castration as a deterrence punishment for rape in Malaysia and we hope that our recommendation will reduce the number of rape cases and to stop them from destroying other people's life especially the children as they are still young and innocent. We will study the feasibility of castration as an alternative punishment for rape offenders in Malaysia in compliance with Section 376 of the Penal Code and will examine the punishment of chemical and surgical castration in the United States. It will be significant to the lawmakers to take into consideration our research proposal on castration to be included as an alternative punishment for rape under the Penal Code.